2023
DOI: 10.3892/etm.2023.11785
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from MDR cells induce cetuximab resistance in CRC via PI3K/AKT signaling‑mediated Sox2 and PD‑L1 expression

Abstract: The anti-EGFR antibody cetuximab is used as a first-line targeted therapeutic drug in colorectal cancer. It has previously been reported that the efficacy of the EGFR antibody cetuximab is limited by the emergence of acquired drug resistance. In our previous study the transmissibility effect of exosomes from drug resistant tumor cells to sensitive tumor cells was identified. It can therefore be hypothesized that drug resistant cells might affect neighboring and distant cells via regulation of exosome compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Exosomal miR-21 and IL-6 produced from CAFs together increased MDSC formation in oesophageal squamous cell carcinoma by activating STAT3, which made tumour cells resistant to cisplatin [234]. Furthermore, SOX2 and PD-L1 expression was mediated by PI3K/Akt signalling pathway activation and was shown to be a mechanism by which exosomes from CRC/MDR cells may increase cetuximab resistance in KRAS wild-type cells [235].…”
Section: Tumour Microenvironmentmentioning
confidence: 98%
“…Exosomal miR-21 and IL-6 produced from CAFs together increased MDSC formation in oesophageal squamous cell carcinoma by activating STAT3, which made tumour cells resistant to cisplatin [234]. Furthermore, SOX2 and PD-L1 expression was mediated by PI3K/Akt signalling pathway activation and was shown to be a mechanism by which exosomes from CRC/MDR cells may increase cetuximab resistance in KRAS wild-type cells [235].…”
Section: Tumour Microenvironmentmentioning
confidence: 98%
“…By characterizing these exosomes and elucidating their role in mediating drug resistance, they provided valuable insights into potential therapeutic targets. Furthermore, their findings underscored the involvement of the PI3K/AKT signaling pathway and stem cell-associated genes in promoting cetuximab resistance, highlighting the complexity of CRC resistance mechanisms [96].…”
Section: Ccsc and Drug Resistancementioning
confidence: 99%
“…In a colon cancer model, exosomes could transfer cetuximab resistance to sensitive cells by downregulating PTEN and increasing p-Akt levels [226]. Another study found that exosomes released from MDR colorectal cancer cells increased PD-L1 and Sox2 expression in recipient cells via PI3K/AKT activation and led to the expression of stem-cell-associated markers, resulting in cetuximab resistance [227]. Bevacizumabresistant colorectal cancer cells and their respective exosomes carry increased levels of the lncRNA SNHG11.…”
Section: Immunotherapy and Targeted Therapymentioning
confidence: 99%